The general concept of disease. Revision, criticism and proposal. First part - Peña, Adolfo (2002)
This is the first of a three part series dedicated to analyze one of the central concepts of medicine: disease. Our first mission will be to revise the diverse and disperse disease definitions. This historical and epistemological revision will stress the naturalist-normativistic dichotomy and Sadegh-Zadeh’s novel mathematical proposal.